2022
DOI: 10.32322/jhsm.1011537
|View full text |Cite
|
Sign up to set email alerts
|

Medical device related pressure injuries in COVID-19 patients followed up in an intensive care unit

Abstract: Aim:The aim of this study is to determine the prevalence of medical device-related pressure injuries in COVID-19 patients. Material and Method:This study was conducted with a cross-sectional and retrospective design. The data of 436 patients who were followed up and treated in the Anesthesia and Reanimation Intensive Care Unit with the diagnosis of COVID-19 disease between 11.03.2020-31.02.2021 in a Training and Research Hospital in İstanbul were included in the study. The sample of the study consisted of 32 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In a study carried out by Jones et al (13), barotrauma was found to be a frequent complication in severe COVID-19 patients, and it was predicated that ventilation support to these patients should be adjusted in optimal level. It can be claimed that the patients included in the present study developed pneumothorax, pneumomediastinum and subcutaneous emphysema secondary to barotrauma (9,11).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…In a study carried out by Jones et al (13), barotrauma was found to be a frequent complication in severe COVID-19 patients, and it was predicated that ventilation support to these patients should be adjusted in optimal level. It can be claimed that the patients included in the present study developed pneumothorax, pneumomediastinum and subcutaneous emphysema secondary to barotrauma (9,11).…”
Section: Discussionmentioning
confidence: 80%
“…Pulmonary parenchymal damage among COVID-19 patients brings about complications related to barotrauma (9)(10)(11). In a study carried out by Jones et al (13), barotrauma was found to be a frequent complication in severe COVID-19 patients, and it was predicated that ventilation support to these patients should be adjusted in optimal level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the COVID-19 pandemic, the importance of MV has emerged once again due to respiratory support, which is one of the most important parts of the treatment for respiratory failure in patients with COVID-19 pneumonia (14,36,37). This situation was seen with the increase of publications on MV during the pandemic period.…”
Section: Discussionmentioning
confidence: 99%